Investigating the relationship of direct and indirect skills as listening strategies / Melissa Malik ... [et al.] - Malik, Melissa; Md Raus, Fatimah Azzahra; Abdul Rahim, Nur Natasha Eliana; Rosly, Ahmad Rusidy; Suhaimi, Abdul Rauf (Universiti Teknologi MARA, Kedah, 2024)
Listening has played a critical component of the educational process, especially in the ESL setting as it can help the learners to understand comprehensively and to respond accordingly. However, there are some strategies that can be used to overcome the obstacles. This study aimed to explore ESL learners’ perceptions on direct skill and indirect skill used as listening strategies. This study also sought to investigate the relationship between direct skill and indirect skill used as listening strategies. The data was gathered using a quantitative survey featuring a 5-point Likert scale rooted from Tuyen et al. 's (2020). 122 post-secondary ESL learners from a public university responded to this survey. Findings revealed that for direct skills, the majority of the participants were willing to inform the speakers when having difficulties in understanding the discussed topic, pay attention to the speaker's voice and try their best to identify the speaker’s main points. Meanwhile, for indirect skills, a majority of participants agree that they would guess speakers’ intention, focus on the speaker's intonation and identify the meanings of unfamiliar words while listening. It also revealed a strong positive relationship between direct and indirect skills. Therefore, to enhance listening comprehension skills, ESL educators are encouraged to introduce and promote the application of both direct and indirect strategies. Additionally, learners need to recognize and apply direct and indirect listening techniques when encountering listening challenges.